Negative plant‐phyllosphere feedbacks in native Asteraceae hosts – a novel extension of the plant‐soil feedback framework. (4th July 2017) - Whitaker, Briana K.; Bauer, Jonathan T.; Bever, James D.; Clay, Keith
Abstract: Over the past 25 years, the plant‐soil feedback (PSF) framework has catalyzed our understanding of how belowground microbiota impact plant fitness and species coexistence. Here, we apply a novel extension of this framework to microbiota associated with aboveground tissues, termed 'plant‐phyllosphere feedback (PPFs)'. In parallel greenhouse experiments, rhizosphere and phyllosphere microbiota of con‐ and heterospecific hosts from four species were independently manipulated. In a third experiment, we tested the combined effects of soil and phyllosphere feedback under field conditions. We found that three of four species experienced weak negative PSF whereas, in contrast, all four species experienced strong negative PPFs. Field‐based feedback estimates were highly negative for all four species, though variable in magnitude. Our results suggest that phyllosphere microbiota, like rhizosphere microbiota, can potentially mediate plant species coexistence via negative feedbacks. Extension of the PSF framework to the phyllosphere is needed to more fully elucidate plant‐microbiota interactions.